The Trouble With Gender. (October 2017) - Johnson, Suzanne
This article discusses gender in relation to culturally derived scripts that contribute to identity confusion. This exploration is aided by the postmodernist perspectives of several authors who critique the notion of gender as a fixed aspect of identity. Gender is considered as a projection of cultural scripting, which influences the ways in which identity is expressed. Through the lens of Drego's (1996) model of group culture (developed from Berne, 1963), the author offers suggestions for working with internalized cultural influences that are expressed in gendered behaviors and given gendered meaning. She proposes that psychotherapists consider their own gender scripting and, for the benefit of therapeutic practice, develop their own psychological androgyny.